Anatomia comparada de duas variedades de cafeeiro em Minas Gerais - Sartori, Luana de Jesus (2023)
The study of leaf anatomy of coffee trees from different locations is important to understand the adaptation mechanisms of varieties to environmental conditions. Since leaves have great plasticity, they act as indicators of edaphoclimatic conditions, as they provide more responses than the root and stem. Understanding the anatomy can help producers to choose certain varieties in the most appropriate places, in addition to contributing to the creation of cultivars that are more tolerant to environmental stress. The experiment was conducted at the Experimental Units of the Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG) in the cities of Patrocínio and Monte Carmelo. Each location has coffee plantations with the “Catiguá MG3” and “Sarchimor” varieties, implanted in 2017. However, in Monte Carmelo drip irrigation is used while Patrocínio is conducted in dryland. This work aimed to verify changes in leaf anatomy between the same variety of coffee from different locations, and between the two varieties from the same location. For this purpose, completely expanded leaves from the third node were collected for the assessment of leaf anatomy at the Laboratório de Anatomia Vegetal (DBI) of the Universidade Federal de Lavras (UFLA). Through this, it was verified that the varieties of the two places presented characteristics that confer tolerance to high temperatures. In Monte Carmelo, the individuals presented greater thickening of the cuticle, while in Patrocínio, greater thickening of the palisade parenchyma. In Monte Carmelo, a larger vessel and stomatal pore diameter was also observed, indicating greater transpiration and translocation of water and minerals, with irrigation being a possible explation for the differences found.